Hindi translation and modification of modified JOA score for cervical myelopathy and its validation for the Indian population - Nishant Nishant; Varun Kumar Agarwal; Praveen Garg; Thimmappa Somashekarappa (Indian Spine Journal, 2024)
Objective: To do a cross-cultural adaptation and validation of the translated Hindi version with Indian modification of the Japanese Orthopedic Association (In-mJOA-H) score for cervical myelopathy. Background: Indian modification of the Japanese Orthopedic Association (In-mJOA-H) score has never been translated and studied in any vernacular language. This is one of the biggest limitations in assessing disease severity where most of the population is speaking Hindi or other regional languages. Materials and Methods: A cross-sectional study of 193 patients, from November 2020 to May 2021, with cervical myelopathy or neck pain with radiculopathy was done. The acceptability, validity, responsiveness, reproducibility, and cross-cultural adaptation were evaluated for the Hindi version (In-mJOA-H). Results: A strong correlation was found between In-mJOA-H with the English version and its individual component of the English version Indian modification of the JOA scale (In-mJOA-E). Conclusion: Good acceptability, validity, responsiveness, and reproducibility were established for the Hindi version (In-mJOA-H) with Indian modifications and its correlation to the English version Indian modification of the JOA scale (In-mJOA-E).